ICT and Special Needs. (Journal of Parents and Teachers, 2014)
The use of ICT in the educational process favors attention to diversity in the classroom and, especially, the attention to students with SEN. The article proposes technological resources for deaf students, students with visual deficit, as well as educational projects and organizations of interest.
Keywords: ICT; attention to diversity; attention to students with SEN; resources.